Mitochondrial Deformation During the Cardiac Mechanical Cycle. Issue 1 (10th October 2018) - Rog‐Zielinska, E. A.; O'Toole, E. T.; Hoenger, A.; Kohl, P.
ABSTRACT: Cardiomyocytes both cause and experience continual cyclic deformation. The exact effects of this deformation on the properties of intracellular organelles are not well characterized, although they are likely to be relevant for cardiomyocyte responses to active and passive changes in their mechanical environment. In the present study we provide three‐dimensional ultrastructural evidence for mechanically induced mitochondrial deformation in rabbit ventricular cardiomyocytes over a range of sarcomere lengths representing myocardial tissue stretch, an unloaded "slack" state, and contracture. We also show structural indications for interaction of mitochondria with one another, as well as with other intracellular elements such as microtubules, sarcoplasmic reticulum and T‐tubules. The data presented here help to contextualize recent reports on the mechanosensitivity and cell‐wide connectivity of the mitochondrial network and provide a structural framework that may aide interpretation of mechanically‐regulated molecular signaling in cardiac cells. Anat Rec, 302:146–152, 2019. © 2018 The Authors. The Anatomical Record published by Wiley Periodicals, Inc. on behalf of American Association of Anatomists.